2015
DOI: 10.1007/s00408-015-9783-x
|View full text |Cite
|
Sign up to set email alerts
|

Dry Lung as a Physical Model in Studies of Aerosol Deposition

Abstract: A new physical model was developed to evaluate the deposition of micro- and nanoaerosol particles (NAPs) into the lungs as a function of size and charges. The model was manufactured of a dry, inflated swine lung produced by Nasco company (Fort Atkinson, WI). The dry lung was cut into two lobes and a conductive tube was glued into the bronchial tube. The upper 1-2-mm-thick layer of the lung lobe was removed with a razor blade to expose the alveoli. The lobe was further enclosed into a plastic bag and placed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Its operation is based on electrohydrodynamic spraying of water and ethanol solutions followed by gas-phase neutralization. Nanoaerosol particles (NAPs) generated by this technique bear a few charges on each particle [ 48 ]. Earlier, we showed that charged NAPs were deposited within a dry swine lung model twice as efficiently as neutral NAPs of the same size [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its operation is based on electrohydrodynamic spraying of water and ethanol solutions followed by gas-phase neutralization. Nanoaerosol particles (NAPs) generated by this technique bear a few charges on each particle [ 48 ]. Earlier, we showed that charged NAPs were deposited within a dry swine lung model twice as efficiently as neutral NAPs of the same size [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…NAPs from the generator bear several charges on each particle. 10 The size distribution of the NAPs from the generator was characterized by the same SMPS (equipped with an input impactor having a cutoff size of d 50 = 664 nm) after the particles were passed through the soft X-ray charger in order to equilibrate them to the Boltzmann distribution. The mass concentration of NAPs was measured by a piezobalance dust monitor (Kanomax, model 3521, Andover, NJ).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The distribution of charges on the NAPs thus generated deviates substantially from the Boltzmann distribution in which only a small fraction of NAPs is charged (e.g., ∼40% of NAPs, 100 nm in diameter, have one elementary charge). NAPs from the generator bear several charges on each particle . The size distribution of the NAPs from the generator was characterized by the same SMPS (equipped with an input impactor having a cutoff size of d 50 = 664 nm) after the particles were passed through the soft X-ray charger in order to equilibrate them to the Boltzmann distribution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations